2020
DOI: 10.1161/jaha.119.015513
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for Tranilast in Regulating NLRP3 Ubiquitination, Vascular Inflammation, and Atherosclerosis

Abstract: Background Aberrant activation of the NLRP 3 (nucleotide‐binding oligomerization domain, leucine‐rich repeat–containing receptor family pyrin domain‐containing 3) inflammasome is thought to play a causative role in atherosclerosis. NLRP 3 is kept in an inactive ubiquitinated state to avoid unwanted NLRP 3 inflammasome activation. This study aimed to test the hypothesis that pharmacologic manipulating of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…Additionally, CY-09, OLT1177, 3,4-methylenedioxy-β-nitrostyrene (MNS), N-[3′,4′-dimethoxycinnamoyl]-anthranilic acid (Tranilast), and oridonin are also specific inhibitors of NLRP3 inflammasome 33 , 117 . Remarkably, a recent study found that tranilast exhibited antivascular inflammation and anti-atherosclerosis properties via increasing NLRP3 ubiquitination and impeding NLRP3 inflammasome activation 118 . Besides, oridonin was found to blunt endothelial inflammation through restraining the activation of MAPK and NF-κB signaling pathways 119 .…”
Section: Clinical Drugs and Nlrp3 Inflammasome And Endothelial Dysfunmentioning
confidence: 99%
“…Additionally, CY-09, OLT1177, 3,4-methylenedioxy-β-nitrostyrene (MNS), N-[3′,4′-dimethoxycinnamoyl]-anthranilic acid (Tranilast), and oridonin are also specific inhibitors of NLRP3 inflammasome 33 , 117 . Remarkably, a recent study found that tranilast exhibited antivascular inflammation and anti-atherosclerosis properties via increasing NLRP3 ubiquitination and impeding NLRP3 inflammasome activation 118 . Besides, oridonin was found to blunt endothelial inflammation through restraining the activation of MAPK and NF-κB signaling pathways 119 .…”
Section: Clinical Drugs and Nlrp3 Inflammasome And Endothelial Dysfunmentioning
confidence: 99%
“…Tranilast, a tryptophan metabolite analog, binds to NACHT domain of NLRP3, preventing NLRP3-NLRP3 interaction and alleviating the symptoms of gouty arthritis, cryopyrin-associated autoinflammatory syndromes, and type 2 diabetes ( 115 ). In addition, tranilast increases K63-linked ubiquitination of NLRP3 ( 116 ).…”
Section: Small Molecules and Phytochemicals Regulating The Nlrp3 Inflmentioning
confidence: 99%
“…On the one hand, the inflammatory reaction can promote the rupture of foam cells after phagocytosis of lipids, releasing more lipid content that accelerates the increase in the atherosclerotic core volume; on the other hand, the inflammatory reaction can also cause carotid vascular remodeling, which leads to further narrowing of the vascular lumen. Studies have shown that administration of tranilast in an animal model of vascular stenosis can reduce vascular remodeling and thus improve vascular stenosis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%